Saint-Pierre-et-Saint-Paul de Ferrières-en-Gâtinais. Le destin d'une abbaye de ses origines au XIIIe siècle - Coulangeon, Cécile (Hortus Artium Medievalium, 2018)
Abstract The former St Peter and St Paul's abbey of Ferrières-en-Gâtinais (France, Loiret department) is one of the oldest Merovingian abbeys attested in ancient sources from the seventh century. This monastery is a very relevant example that allows us to observe the creation of a monastic complex in the Merovingian period, around a first oratory whose traces probably remain in the walls of the Chapel of Our Lady of Bethlehem, and its architectural evolution in the course of the first millennium with the gradual establishment of a configuration with two churches placed in the extension of one the other. The first abbey church is probably built between 821 and 828, in the time of abbot Aldric, as an octagonal rotunda whose memory has been preserved within the Gothic reconstruction of the monument. The latest research allows us to consider possible funerary functions because of this centered plan, a hypothesis that remains to be verified by future excavations on the site.